Biomechanical assessment in HAV treatment - Ma Ángeles Rodríguez Personat; Fernando Chacón Giráldez; Lidia Carvajal Moreno; Ana Juana Pérez Belloso (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2021)
Hallux Abductus Valgus (HAV) is a pathology that affects the first metatarsophalangeal joint, in which there is a medial displacement of the metatarsal and a lateral deviation of the hallux, causing joint dysfunction and disability in the patient. There are two types of treatments for this condition (conservative and surgical), and both require an exhaustive biomechanical assessment, since biomechanics are the main cause of this deformity. The main objective of the article is the development of a biomechanical examination and assessment algorithm to be carried out systematically in patients with HAV.